2020
DOI: 10.1186/s12882-020-02019-w
|View full text |Cite
|
Sign up to set email alerts
|

Association among kidney function, frailty, and oral function in patients with chronic kidney disease: a cross-sectional study

Abstract: Background: Chronic kidney disease (CKD) involves many factors that can cause frailty and oral hypofunction. We aimed to investigate the prevalence of frailty and oral hypofunction and to examine the associations among kidney function, frailty, and oral function in adults with CKD in Japan. Methods: This cross-sectional study was conducted at two institutions. The participants included 109 patients with CKD stages 3-5 who visited outpatient clinics or were admitted for inpatient treatment. Frailty was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
9
1
Order By: Relevance
“…In the present study, there was no direct association between ODK and frailty, which was different from other studies 33,34 . The reason may depend on a mediator of nutritional status.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, there was no direct association between ODK and frailty, which was different from other studies 33,34 . The reason may depend on a mediator of nutritional status.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, there was no direct association between ODK and frailty, which was different from other studies. 33,34 The reason may depend on a mediator of nutritional status. The previous studies did not include nutritional status to assess the association between ODK and frailty.…”
Section: Discussionmentioning
confidence: 99%
“…The main finding of the present study was that the severity of xerostomia was an independent factor associated with physical frailty, even after adjusting for the effects of confounding factors, such as general health status and oral function, which were reported to be associated with physical frailty in previous multivariate F I G U R E 2 Correlation between the Summated Xerostomia Inventory score and the amount of resting saliva analyses. 4,10,39,40,44,45 Ramsay et al 16 reported that the accumulated xerostomia status was associated with physical frailty among older British men. We confirmed similar findings in this study, which targeted community-dwelling men and women in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The models included the severity of physical frailty as the outcome. Based on previous studies, [11][12][13]17,[37][38][39][40][41] the following variables were considered covariates: age, sex, number of comorbidities, polypharmacy, smoking status, cognitive impairment, wellbeing status, BMI, educational status, number of present teeth, articulatory oral motor skill and chewing ability. We prepared the directed acyclic graph (DAG) to identify the variables that required adjustment in the multivariable models and thereby minimise the effects of confounding bias and avoid over-adjustment of the variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…It was reported that there is a high prevalence of frailty in patients with chronic kidney disease (CKD) and a significant association between frailty and motor skills, affecting swallowing in patients with CKD (Kosaka et al, 2020 ). Kamijo et al ( 2018 ) reported that in peritoneal dialysis patients, low tongue pressure is a risk factor for sarcopenia.…”
Section: Introductionmentioning
confidence: 99%